Speed of Adjustment Capital Structure - Sibuea, Ely Yulianita; Yulianto, Arief (Management Analysis Journal, 2018)
The aim of this study is to analyze the effect of company size variables, asset growth, asset structure and business risk against capital structure adjustment speed with dynamic approach. The number of samples in this study was 63 companies by using purposive sampling method. Multiple regression method with fixed effect model was used as data analysis in this study. The results of this study indicate that company size and asset structure have positive significant effect on capital structure adjustment speed, whereas asset growth has significant negativeeffect on capital structure adjustment speed and business risk does not have significanteffect on capital structure adjustment speed.